2019
DOI: 10.1017/s1041610218002168
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the effect of reminiscence therapy for people with dementia

Abstract: Background:The main objective of this study was to conduct a meta-analysis to identify the effects of reminiscence therapy in people with dementia (PWD).Methods:A systematic search of randomized controlled trials (RCTs) was conducted using bibliographic databases. A total of 157 original published studies were identified in the search, and 24 complete articles were included in the final review to check for the level of evidence. Two of the study authors independently assessed the quality of the included studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 41 publications
(69 reference statements)
7
75
1
Order By: Relevance
“…Although a recent systematic review found that reminiscence therapy reduced depression and BPSD as well as improved QoL [30], our study showed that MM did not significantly affect QoL and BPSD because of small sample size. In our study, the planned sample size was 97.…”
Section: Discussioncontrasting
confidence: 90%
“…Although a recent systematic review found that reminiscence therapy reduced depression and BPSD as well as improved QoL [30], our study showed that MM did not significantly affect QoL and BPSD because of small sample size. In our study, the planned sample size was 97.…”
Section: Discussioncontrasting
confidence: 90%
“…Men and women aged 65 years or older; Diagnosis of probable or possible AD based on the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association scale; 17 Mild-to-moderate stage of dementia based on a Clinical Dementia Rating (CDR) scale score of 1.0 or 2.0; and Willingness to participate in the study and provision of informed written consent.…”
Section: Participantsmentioning
confidence: 99%
“…In addition, communication in these groups can help people avoid social isolation, aiding the formation of social behaviors. 6,9 In the past 30 years, a large number of studies conducted have reported positive outcomes of RT for treating dementia in terms of a range of variables, including cognitive function, [10][11][12][13] emotions, 10,[13][14][15][16]17 activities of daily living, 13,17 well-being, 16 life satisfaction, 16,18 communication, 19 and ego-integrity. 20,21 However, some of these studies focused on individual reminiscence, often with small sample sizes, and some did not include a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Gibson described the uses of reminiscence in dementia care as a therapeutic intervention, an enjoyable activity, or possibly a combination of both. Reminiscence practitioners can use reminiscence as an activity program, which positions the patients’ experiences and memories at the center of the activity . Uses of reminiscence in mild dementia care can fall into two categories: Informal and formal uses .…”
Section: Resultsmentioning
confidence: 99%
“…In the context of mild dementia care, informal uses of reminiscence may aim to provide a basis for other groups, increase interactions with peers, and find commonalities between patients . The formal uses of reminiscence as a therapeutic tool in mild dementia care have been shown in many systematic reviews and meta‐analyses to be a worthwhile strategy for improving depressive symptoms, cognitive functions, communication skills, and social inclusion . Other formal uses of reminiscence have been reported to include enhanced well‐being, raised self‐esteem, increased sense of personal identity, and reduction in anxiety levels .…”
Section: Resultsmentioning
confidence: 99%